The effect of corporate social responsibility on financial performance in Nigeria: a multi-dimensional analysis - Karaye, Yusuf Ibrahim; Ishak, Zuaini; Che Adam, Noriah (2016)
This study examines the relationship between corporate social responsibility (CSR) dimensions and financial performance in the Nigerian listed companies. The population of the study is 196 listed companies in the Nigerian stock exchange. The sample is determined to be 130 companies out of which 99 responses were received. The study adopts survey design and structural equations modelling (SEM) was conducted using smart PLS 2.0 software. It was found that customer, employee and investor relations have a positive significant effect on financial performance of Nigerian listed firms. Future studies are encouraged to examine the effect of other CSR dimensions that are not examined in the present study, on financial performance.